Analisis Nilai Percepatan Tanah Maksimum dan Klasifikasi Kelas Situs di Kota Serang Provinsi Banten - Widjayanti, Retno Yogi; AL HS, Usholl Auli; Rahman, Adtya Setyo; Permana, Dimas; Alfiandy, Solih (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2025)
Serang City exhibits a high level of seismic vulnerability due to its tectonic position near the convergent boundary between the Indo – Australian and Eurasian plates. Additionally, the local geological conditions, which are dominated by alluvial deposits, make seismic waves more susceptible to amplification and resonance, thereby increasing earthquake hazard potential. The objective of this research is to identify site class characteristics and calculate surface PGA values to assess seismic threat levels in the urban area. The data used include ground acceleration values from microzonation maps, local geological information, and regional seismic parameters. The analysis was conducted by classifying site conditions based on the average shear wave velocity to a depth of 30 meters (Vs30), and by estimating surface PGA values using local amplification factors. The results indicate that most areas of Serang City are classified as SE site class (soft soil), followed by SD site class (medium soil), predominantly in the southwestern part of the city. Surface peak ground acceleration values range from 0.84 to 0.91 g, which are considered very high. These findings suggest that all six districts in Serang City–Serang, Cipocok Jaya, Taktakan, Curug, Kasemen, and Walantaka–are at significant seismic risk in the event of an earthquake. Therefore, appropriate risk mitigation strategies are essential, including the reinforcement of spatial planning systems, the design of earthquake – resistant structures, and the development of more detailed seismic microzonation maps.